EFEKTIFITAS MEDIA POSTER TERHADAP PENINGKATAN PENGETAHUAN TENTANG KESEHATAN GIGI (Studi pada siswa-siswi kelas V SD Negeri di Kelurahan Saigon) - Jumilah, Jumilah; Jauhari, Abdul Haris; Ridha, Abduh (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Background: Riskesdas 20013 in west Kalimantan showed a high score of DMF-T in childrens aged 12 years is 6,2 which means every childs aged 12 years is 6,2 which mean avery child aged 12 years. occurred tooth decas as much as 6 teeth, the program that have been implemented for this is preventif and rehabilitative efforts. While effort promotive still very low due two lack of power. Therefore the poster felt very affective in conveying the massage of dental heath toimprove student knowledge, where knowledge is the initial capital of behavior change.Objective: To determine the effectiveness of the poster to the knowledge about dental health study in fifth grade elementary school students in Village Saigon, Pontianak.Methods: The designe of this study is experimental. The designe of non-random randomized control group pre-test designe. The member of respondens in this study of 30 people white different treatments. Data collection techniques used were interviews. Data collection instrument used are quisioner to prove the hypothesis Test T .Results: There is defference in knowledge (P value = 0,000) betwen before and after exposure to the media poster 7 days, There is defference in knowledge (P value = 0,000) betwen before and after exposure to the media poster 14 days, There is defference in knowledge (P value = 0,000) between intervention group and the control group 7 days on posters media exprosure given in the elementary school fifth grade students Village Saigon. There is defference in knowledge (P value = 0,000) between intervention group and the control group 14 days on posters media exprosure given in the elementary school fifth grade students Village Saigon. Conclusion: there is in knowladge in the fifth grade public school students Village Saigon after exprosure to the poster for 7 days and 14 days, then the poster can be made tool to halp the promotion of health in order to improve health especially the health of the teeth and mouth.Key Word : Poster, knowledge, and caries dentis